The impact of primary care physicians' education about easy skin lesion diagnosis algorithm on skin cancers screening effects - Kamila Matyka; Izabela Uniłowska; Aleksandra Karwańska; Ewa Kojder; Arsen Dolenha; Aleksandra Kulbat; Yuliia Dovzhuk; Justyna Ochał; Anna Ferschke; Aleksandra Matyszewska (Kazimierz Wielki University, 2023)
Introduction and purpose:  Number of new cases of skin cancers grows every year. Melanoma malignum is responsible for approximately 75 percent of death from skin cancer. General practitioners are often first medical professionals who see patients with suspicious skin lesions. Early diagnosis can benefit in improving survival rates. Dermoscopy is a useful tool for dermatological diagnostic purposes not only for dermatologists, but also for Primary Care Physicians.This review aims to analyze the role of easy 3-step Triage Amalgamated Dermoscopy Algorithm performed by family medicine physicians in skin cancers detection.  Material and methods: We searched PubMed database in order to collect relevant studies about skin cancers diagnoses by family medicine physicians using dermoscopy algorithms.  Results: An analysis of multiple studies shows that short Triage Amalgamated Dermoscopy Algorithm training taken by primary care physicians resulted in better diagnosis accuracy of skin cancer identification. After education about 3 benign skin lesion patterns and 7 signs of potential malignancy general practitioners reported more confidence in the diagnostic process and both sensitivity and specificity of examination increased post-training. Conclusion: Teaching Primary Care Physicians how to diagnose patients with suspicious skin lesions using Triage Amalgamated Dermoscopy Algorithm may have a beneficial effect on increasing the number of early-diagnosed skin cancers which may result in improving survival rates.